PENGARUH GAJI, INTENSIF, KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BULOG (SUB DIVRE WILAYAH V) KEDU - Suhaeli, Dahli (Jurnal Analisis Bisnis Ekonomi, 2007)
Performance employees do not get out of appraisal, which employees Performance Appraisal can be improved by using factors able to motivate employees. Research target is to know variable influence Salary, Incentive, Leadership, Motivation and Environment Work to Performance Appraisal Employees. Elementary at amount of Bulog employees (Regional Sub Divre of V) Kedu which is small relative, hence in this research can be expressed that population at the same time as sample, that is counted 30 employees people. Method intake of sample in this research use Saturated Sampling. Method analysis used by Multiple Regressions. Result of analysis which have is to be obtained that, there are influence which ia significant from free variable consisting of Salary variable,  Incentive, Leadership, Motivation and Environment Work to variable tied, Performance Appraisal by simultan and parsial. Dominant  Variable analysis indicate that Leadership variable represent variable owning influence most dominant. Leadership have big enough share to support reaching of company performance.